EXPLOITATION. (30th October 2018) - Ferguson, Benjamin; Veneziani, Roberto
Abstract : The notion of exploitation is prominent in political discourse and policy debates. It is central in analyses of labour relations, especially focusing on the weakest segments of the labour force including women and children (International Labour Office2017a, 2017b ). It features in controversies on surrogate motherhood (Wood1995 ; Wertheimer1996 ), and on drug-testing and the price of life-saving drugs, especially in developing countries.